2002
DOI: 10.1177/112067210201200105
|View full text |Cite
|
Sign up to set email alerts
|

Increased Corneal Thickness in Active Behçet's Disease

Abstract: Behçet's patients with active ocular involvement have a thicker CCT than patients with inactive ocular involvement. There was no difference in CCT between controls and patients with no ocular involvement. The CCT of patients with active ocular involvement returned to nearly normal after treatment. CCT must be taken into account when developing a managing and following approach for Behcet's patients with active ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…One study in Behçet panuveitis patients revealed a significantly increased corneal thickness (5%) in patients with active inflammation compared to the unaffected side and to the control group [3] . The magnitude of increase was higher in our patients' series, with a 10% increase in normal thickness compared to the unaffected side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in Behçet panuveitis patients revealed a significantly increased corneal thickness (5%) in patients with active inflammation compared to the unaffected side and to the control group [3] . The magnitude of increase was higher in our patients' series, with a 10% increase in normal thickness compared to the unaffected side.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with active anterior uveitis, an increase in corneal thickness is frequently seen due to the presence of endothelial precipitates associated with a corneal edema [3,4] . IOP measurements are required during acute inflammation to exclude elevated IOP and may help to detect an underlying association as for example IOP is elevated in herpetic anterior uveitis or in ocular sarcoidosis.…”
mentioning
confidence: 99%
“…Although the aetiopathogenesis of the disease has not yet been clarified, several mechanisms such as genetics, infection, immunoglobulin, immune complexes and antibodies have all been suggested as the causes of BD. 4,6 It affects almost every tissue and organ in the body without exception, including the cornea, 7 inner ear 8 and the lung. 9 The intermittent nature and the lack of consistent response to therapy make the underlying aetiology difficult to define.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Anterior segment inflammation may affect corneal endothelium; following that, some corneal changes may occur in uveitic eyes. [3][4][5][6][7][8][9][10] The response of corneal endothelium can be assessed clinically by central corneal thickness (CCT) measurements. 11,12 In the present study, we measured CCT in eyes with active and inactive ocular involvement in BD and compared the results with age-matched controls.…”
mentioning
confidence: 99%